The Aztecs: people of the sun - Caso, Alfonso, 1896-1970.; Covarrubias, Miguel, 1904-1957; Dunham, Lowell, 1910-2001 (Norman: University of Oklahoma Press, 1958)
A study of the social, cultural, and religious customs of this glorious Mexican civilization destroyed by Cortes and his Spanish conquistadores.
Magic and Religion -- The character of the aztec religion -- The creation of the gods -- The four directions -- The creation of man -- Man, the collaborator of the gods -- The creator gods -- The raiment of the gods -- Complexity of the aztec pantheon -- Tezcatlipoca -- The worship of the sun, the moon, and the stars -- The gods of fire -- The gods of water and of vegetation -- The earth gods -- The gods of death -- The paradises and the hells -- The calendars -- Priestly organization -- The people of the sun
Translation of El pueblo del sol.
Includes bibliographical references and index.
NLJCols20082021
Keywords: Aztecs; Aztec mythology; Aztecs; Aztec mythology; Aztecs; Aztecs